2018
DOI: 10.1002/jcp.27467
|View full text |Cite
|
Sign up to set email alerts
|

ceRNA network construction and comparison of gastric cancer with or without Helicobacter pylori infection

Abstract: Gastric cancer (GC) is a lethal disease, and among its variety of etiological factors, Helicobacter pylori (H. pylori) infection is the strongest risk factor. However, the genetic and molecular mechanisms underlying H. pylori-related GC need further elucidation. We investigated the competing endogenous RNA (ceRNA) network differences between H. pylori (+) and H. pylori (−) GC. The long noncoding RNA (lncRNA), microRNA (miRNA), and messenger RNA (mRNA) expression data from 32 adjacent noncancerous samples and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…For the first time, we found that these four novel lncRNAs play a vital role in LUAD. Studies have shown that highly expressed AP002478.1 has a poor prognosis in gastric cancer and hepatocellular carcinoma [35,36], and our study in LUAD also showed the same results, this suggests that AP002478.1 plays an important role as a carcinogenic factor in many kinds of cancers. LINC00518 was first discovered and developed as a non-invasive 2-gene molecule in the detection of cutaneous melanoma [37].…”
Section: Discussionsupporting
confidence: 83%
“…For the first time, we found that these four novel lncRNAs play a vital role in LUAD. Studies have shown that highly expressed AP002478.1 has a poor prognosis in gastric cancer and hepatocellular carcinoma [35,36], and our study in LUAD also showed the same results, this suggests that AP002478.1 plays an important role as a carcinogenic factor in many kinds of cancers. LINC00518 was first discovered and developed as a non-invasive 2-gene molecule in the detection of cutaneous melanoma [37].…”
Section: Discussionsupporting
confidence: 83%
“…Next, the relationships between the lncRNAs and miRNAs were defined using the miRcode database (http://www.mircode.org). To further investigate the roles of DEmiRNAs in GBM, we used the following three databases to predict the target genes of the miRNAs:miRTarBase, TargetScan, and miRDB 12 . Then, to further ensure the reliability of the constructed ceRNA network, we compared the predicted target miRNAs and mRNAs with the dysregulated miRNAs and mRNAs in the TCGA or GEO GBM samples and retained only the data of the overlapping miRNAs and mRNAs and their interaction pairs for further analysis.…”
Section: Experimental Methods and Designmentioning
confidence: 99%
“…forming a lncRNA-miRNA-mRNA ceRNA network, which can regulate multiple signaling pathways, including the HIF-1α pathway (74,75). In addition, the HIF-1α-mediated hypoxia-induced upregulation of lncRNA-NEAT1 in hepatocellular carcinoma regulates the expression of the uridine-cytidine kinase 2 gene, which is associated with low survival rates of patients with liver cancer, by suppressing miR-199a-3p, and ultimately promotes tumor growth (76).…”
Section: Role Of Hif-1 In Non-coding Rna Associated With Cscsmentioning
confidence: 99%